2017
DOI: 10.1002/nbm.3786
|View full text |Cite
|
Sign up to set email alerts
|

31P magnetic resonance fingerprinting for rapid quantification of creatine kinase reaction rate in vivo

Abstract: Purpose To develop a 31P spectroscopic magnetic resonance fingerprinting (MRF) method for fast quantification of the chemical exchange rate between phosphocreatine (PCr) and ATP via creatine kinase (CK). Methods A 31P MRF sequence (CK-MRF) was developed to quantify the forward rate constant of ATP synthesis via CK ( kfCK), the T1 relaxation time of PCr ( T1PCr), and the PCr-to-ATP concentration ratio ( MRPCr). The CK-MRF sequence used a bSSFP-type excitation with ramped flip angles and a unique saturation sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…Therefore, MT needs to be considered because it may affect MRF signal evolution. Previously, a modified Bloch‐McConnell model was used to analyze MT in chemical exchange . In this work, the Bloch‐McConnell model was applied to analyzing the MT between bulk free water and semisolid macromolecule protons, and the results showed that there were nonnegligible biases when using 1P and 2P models (Figure A).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, MT needs to be considered because it may affect MRF signal evolution. Previously, a modified Bloch‐McConnell model was used to analyze MT in chemical exchange . In this work, the Bloch‐McConnell model was applied to analyzing the MT between bulk free water and semisolid macromolecule protons, and the results showed that there were nonnegligible biases when using 1P and 2P models (Figure A).…”
Section: Discussionmentioning
confidence: 94%
“…The measurement is then compared against a simulated dictionary to determine the best matching relaxation rates. MRF has been extended to a host of applications, including perfusion, exchange rate, chemical exchange saturation transfer measurements, and simultaneous imaging of multiple MRI contrast agents . It is worth mentioning that modeling biological tissue often involves more than 1 spin pool (i.e., the bulk tissue water, semisolid macromolecules, and/or dilute mobile proteins and peptides) .…”
Section: Introductionmentioning
confidence: 99%
“…With a larger search space of acquisition parameters, we could achieve better performance, although the resulting optimization problem will be computationally more expensive. Additionally, we could optimize MR fingerprinting experiments to include other tissue parameters, such as apparent diffusion coefficients [66], magnetization transfer [67], [68], etc. Lastly, although the implementation in this paper focused on optimizing the CRB for a fixed number of TRs, there are many other design considerations (e.g., acoustic characteristics of the pulse sequence [69], SAR, total acquisition time, etc), which are important and may be worth including within the optimization framework.…”
Section: Discussionmentioning
confidence: 99%
“…Given the multi-parameter nature of 31 P MT-MRS measurements, and the similarity in measuring T 1 and the exchange-rate modulated T 1app constant in an MT-MRS experiment, an MRF-based MT-MRS method may overcome the low sensitivity and long acquisition time of the conventional 31 P MT-MRS methods. In a recent study, Wang et al developed an MRF-based acquisition strategy for quantification of CK activity (CK-MRF) in rat skeletal muscle (124). Their results showed significantly improved measurement reproducibility in 20-s data acquisition, demonstrating the potential of this new MT encoding strategy.…”
Section: Quantification Of Atp Synthesis Rates By 31p Magnetization-tmentioning
confidence: 99%